A critical analysis of whether BEPS Action 1 resolves issues of source taxation - van Der Westhuizen, Werner (Department of Finance and Tax, 2023)
The digital economy and the challenges it poses to the international tax arena is a swiftly developing area. This dissertation considers the suggestions released by the OECD Pillar 1 dated January 2020 and the UN Article 12B released in August 2020. The digital economy has evolved significantly over the last years and has changed how business operates. Digital enterprises can conduct business across borders without creating a physical presence using information and communication technology. As a result of the increased use of technology in business processes, it has been opined that the digital economy is becoming the economy.1 The challenges posed by the digital economy relate to the ease with which enterprises can conduct business in a jurisdiction without any presence. International tax rules currently require a level of presence in a country before taxes on the business profits can be levied in that jurisdiction. There has been a significant international focus by governments and media on digital enterprises. This is due to the perception that digital companies are under-taxed and that there is a misalignment between where the value is created and where the digital enterprise is subject to tax.2 The OECD/G20 Base Erosion and Profit Shifting project (BEPS) is looking at restoring confidence in the international tax system by taxing profits where value is created. Value creation will therefore be an essential part of the BEPS initiative.3 There are different views regarding the changes to be implemented that are suggested by the OECD Task Force on the Digital Economy (TFDE). One aspect is clear, the changes will have a significant impact on the international tax system for digital enterprises. The dissertation will explore the theories that justify taxation at source. For a tax-compliant culture to exist, it is vital that taxes raised are just.4 It will be shown that the theories that justify taxation at source are relevant to the digital economy and will ensure just taxation at source. To get a clear understanding of source, the concept of source and the current concept under the international tax law, will be discussed. The characteristics of the digital economy and its ability to conclude business in a state without creating a physical presence will be discussed. It will be shown that the characteristics are not new but merely exacerbated by the digital economy. Since the current source concept under international tax law requires a physical presence, the proposals by the OECD Pillar 1 and the UN article 12B will be evaluated. It will be essential to establish whether these proposals address the issues raised by source taxation and the requirement of a physical presence under the Permanent establishment threshold. It is found that the proposals do not address the source issues and are also not based on sound tax policy. The proposal will be at odds with various tax policy principles such as neutrality, equity, and simplicity. The proposals are overly complicated, and valid concerns were raised that countries might receive little or no tax.5 The changes made by BEPS action 1 pillar 2, action 3 (strengthening the CFC rule), 7 (preventing the artificial avoidance of permanent establishment), 8 to 10 (transfer pricing in line with value creation), and 13 (Country by Country Reporting) would largely address the double non-taxation of the digital economy. However; it is also recommended that the changes suggested by the TFDE should not be implemented at this stage, as not enough time has passed since the implementation of BEPS to evaluate the impact clearly.